Analisis Fungsi, Peran, dan Kategori Sintaksis pada Teks Cerita dalam Buku Ajar Bahasa Indonesia Kelas VIII SMP Kurikulum Merdeka - Ulfi Akhyatussyifa; Athia Az-zakia Anwar; Amrina Rosyada; Aminatul Fitroh; Asep Purwo Yudi Utomo; Molas Warsi Nugraheni (Universitas Katolik Widya Karya Malang, 2023)
The study was created to analyze the function, role, and syntax category in the sentences in story texts used in the Indonesian language textbook for class VIII junior high school independent curriculum. The data analysis technique used in this study is a billing technique with a theoretical language approach that focuses on each of the grammatical elements in sentence formation. The data on this analysis is the function, role, and syntax category in direct sentences and indirect sentences. The data source is two-story texts entitled